2017
DOI: 10.3345/kjp.2017.60.11.353
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss screening tool (COBRA score) for newborns in primary care setting

Abstract: PurposeTo develop and evaluate a simple screening tool to assess hearing loss in newborns. A derived score was compared with the standard clinical practice tool.MethodsThis cohort study was designed to screen the hearing of newborns using transiently evoked otoacoustic emission and auditory brain stem response, and to determine the risk factors associated with hearing loss of newborns in 3 tertiary hospitals in Northern Thailand. Data were prospectively collected from November 1, 2010 to May 31, 2012. To devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This is comparable to HICs where PTA screening is mandatory for children over the age of 3 94 95. In contrast, the current review found a few public initiatives75 87 96 that used questionnaire methods, and this implies that mass screening was being done by low-cost tools like questionnaires where resources were limited.…”
Section: Discussionmentioning
confidence: 88%
“…This is comparable to HICs where PTA screening is mandatory for children over the age of 3 94 95. In contrast, the current review found a few public initiatives75 87 96 that used questionnaire methods, and this implies that mass screening was being done by low-cost tools like questionnaires where resources were limited.…”
Section: Discussionmentioning
confidence: 88%
“…Globally, 32 millions of children are estimated to have impaired hearing all around the world and a great majority of them are known to live in countries with low and middle income (1). Prevalence of newborn hearing loss has been stated to be 1-6/1000 infants in every live birth, 3/1000 infants in average, this rate increases up to 10/1000 in infants of risk group in neonatal intensive care units (2,3).…”
Section: Introductionmentioning
confidence: 99%